Estimation of Export Demand Function for Swazi Sugar: A Panel Data Analysis - Maziya, L.K; Tijani, A.A; Masuku, M.B (International Journal of Sustainable Agricultural Research, 2016)
Export demand estimates are important for meaningful export forecasts, planning, and policy formulation that can help improve the performance of the sugar subsector in Swaziland. This study estimated the determinants of export demand for Swazi sugar and measured the impact of the EU reform on Swazi sugar export demand. The study used panel data approach by using annual time series data between the periods 1997 and 2012. An LSDV fixed effects model was employed. Export price, Importer GDP and the EU reform were found to be significant in explaining export demand for Swazi sugar. These variables had coefficients -121.069, and -2.682, respectively, whose signs were against the priori expectation except for export price. The EU reform was found to have an overall positive impact to Swazi sugar export demand with coefficient of 120 816. The study also measured elasticities of the explanatory variables to the export demand of Swazi sugar. Export price, foreign income, producer prices and real exchange rate were found to be inelastic with elasticities of 0.35289, 0.00168, 0.04256 and 0.28572, respectively, for all the markets (SACU, EU, USA and COMESA) pooled together. Explanatory variables in the individual markets were found to be highly elastic. The study, therefore, recommended that Swaziland needs to take advantage of the EU reform and invest more on sugar production as it was not negatively affected. Swaziland also needs to negotiate for the quotas abandoned by those countries heavily affected by the EU reform.